ANALISIS ALIH KODE DAN CAMPUR KODE PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IX.A SMP NEGERI 4 KOTO BARU KABUPATEN DHARMASRAYA TAHUN 2022/2023 - Lismayanti, Br Damanik (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2023)
Analysis of Code Switching and Code Mixing in Indonesian Language Learning in Class IX.A UPT SMP Negeri 4 Koto Baru, Dharmasraya Regency, 2022/2020. This study aims to describe the forms of code switching and code mixing in Indonesian language learning in class IX.A SMP Negeri 4 Koto Baru, Dharmasraya Regency in 2022/2023 and describe how the purpose of code switching and code mixing is in learning Indonesian in class IX. A UPT SMP N 4 Koto Baru. This research is a qualitative research. The data in this study are words, phrases or sentences used by educators and students in learning or formal situations. The method used is descriptive qualitative. The type of data in this study is primary data, because the data obtained is based on personal observations and recordings made at the research location. The results in this study indicate that the forms of code switching in teaching and learning activities are internal code switching and external code switching, and the forms of code mixing can be grouped based on linguistic elements, namely elements of words, phrases and clauses, then based on the type of language, namely internal and external code mixing. The functions of code switching in teaching and learning activities include giving examples, giving orders, or respecting; and the code mixing function, among others, is to add information or quote, emphasize, and give praise. Code switching and code mixing in teaching and learning activities have positive and negative impacts.